The Relationship between Organizational Culture, Job Satisfaction, and Commitment of Lecturers at Universities - Hung Van Tran; Anh Viet Tran; Minh Nguyen Binh Le (Emerging Science Journal, 2023)
Purpose: The study aimed to determine the influence of factors on job satisfaction and the relationship between satisfaction, organizational culture, and the organizational commitment of lecturers at universities in Ho Chi Minh City. Design/Methodology/Approach: This was a quantitative study in which the authors compile theories, analyze and synthesize scales for research concepts, and propose research models. The online survey collected 532 answer sheets from professors and lecturers from universities in Ho Chi Minh City, of which 525 were valid and included in SmartPLS 3 to evaluate the validity and reliability of the scale and to analyze the relationship among the concepts in the suggested model. Findings: The results show that several factors significantly impact employee satisfaction in the field of education, such as job promotion, leadership or supervision, working environment, income, and the job itself. In addition, both satisfaction and organizational culture impact organizational commitment. The study's findings have implications for educational institutions, lecturers, policymakers, researchers, and funding agencies. They highlight the importance of factors like leadership development and organizational culture in enhancing job satisfaction and commitment among lecturers, offering valuable insights for improving the educational environment in Ho Chi Minh City and beyond. Originality: The results aligned with previous studies presented in the literature section. However, this study revealed some specific characteristics of lecturers in universities in Ho Chi Minh City, Vietnam, where lecturers focused on personal development but were committed to the organization via job satisfaction and culture. Doi: 10.28991/ESJ-2023-SIED2-021 Full Text: PDF